دلالة أوصاف القرآن الكريم على أنه واضح المعنى Clear meaning based on holy Quran descriptions - Mohamed Fathy, Mohamed Abdelgelil; Siham Abdullah, Al-Humaidi (2019)
This research includes ten descriptions of the Holy Quran, which shows that Quran explains everything. Whereas every descriptions is separately defined to enhance the referring verse, Significance of the research is to serve the Holly Quran to provide advice to collect all descriptions. As it enhances faith and strengthen certainty. It is one of the basic faith six corners, as the Holly Quran is reference and leader for right path to avoid faults, This study results are that scientific has meaning knowledge of Quran, as those who said that no one can get the meaning. It is considered wrong to be contrary for Sunna and Quran. As people should know that all verses are clear for all nations, so we provide this research.